Mobile Outreach: An Innovative Program for Older Orthopedic Patients in Care Facilities. (6th March 2019) - Switzer, Julie A.; Schroder, Lisa K.
Introduction: The worldwide incidence of fragility fractures is increasing and the greatest burden is borne by the oldest population. Mobile Outreach, an innovative orthopedic-based program providing on-site musculoskeletal care for individuals in nursing care facilities, was implemented as part of our Geriatric Orthopaedic Trauma Program. The objectives of this report are to describe characteristics of patients cared for through Mobile Outreach and to report specific services provided. Program Description: Based from a nonprofit, private hospital that serves as the community's level 1 trauma center and teaching hospital, the Mobile Outreach Program is directed by an orthopedic surgeon with geriatric subspecialization and staffed by a full-time geriatric nurse practitioner. Patients receive care for musculoskeletal concerns and fracture assessments at their nursing care facilities by a Mobile Outreach care provider. Referral for care is from nursing care facilities or as scheduled postoperative follow-up. Results: In 2016, the program treated 458 patients (76% female) in the patients' care settings for a total of 689 visits. The mean age was 81 years (standard deviation = 14; range 25-107). Care of patients included nonoperative fracture care in 100 (22%), postoperative fracture follow-up in 149 (33%), injections for pain management in 184 (40%), and other orthopedic care in 25 (5%). Visits occurred at 88 facilities, mean 7 visits per site (range 1-57). Conclusions: Mobile Outreach was implemented to improve postoperative fracture care in the elderly patients. The program also provides on-site nonoperative fracture care and care of frail elderly individuals with chronic musculoskeletal conditions. This report aims to establish the feasibility of a program focused on the provision of appropriate, coordinated care for older fracture patients in their care facility. Level of Evidence: Level V.